2020
DOI: 10.1016/j.cognition.2020.104241
|View full text |Cite
|
Sign up to set email alerts
|

Perspective taking as virtual navigation? Perceptual simulation of what others see reflects their location in space but not their gaze

Abstract: Other peoples' (imagined) visual perspectives are represented perceptually in a similar way to our own, and can drive bottom-up processes in the same way as own perceptual input (Ward, Ganis & Bach, 2019). Here we test directly whether visual perspective taking is driven by where another person is looking, or whether these perceptual simulations represent their position in space more generally. Across two experiments, we asked participants to identify whether alphanumeric characters, presented at one of eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 61 publications
6
29
0
Order By: Relevance
“…The present work also speaks to the issue of visual perspective taking. A number of people have begun to argue that when humans assume another agent's perspective the representation on which this alternative viewpoint is based is depictive or 'quasi perceptual' [12,13]. Cole and Millett [14], and Cole, Millett [15] have however challenged this claim on theoretical grounds, and in a visual perspective-taking study based on the same stimuli as the present experiment adults also failed to judge that line closer to another agent would appear shorter [16].…”
Section: Discussionmentioning
confidence: 74%
“…The present work also speaks to the issue of visual perspective taking. A number of people have begun to argue that when humans assume another agent's perspective the representation on which this alternative viewpoint is based is depictive or 'quasi perceptual' [12,13]. Cole and Millett [14], and Cole, Millett [15] have however challenged this claim on theoretical grounds, and in a visual perspective-taking study based on the same stimuli as the present experiment adults also failed to judge that line closer to another agent would appear shorter [16].…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, Ward et al [ 16 ] showed that the facilitation effect of perspective taking exists even when the avatar does not look at an object. This difference in the findings may be due to the fact that our avatar was placed facing away from the object with a full body including the head, but the avatar in Ward et al’s [ 16 ] study averted its gaze while its torso faced the object. Thus, the direction of the torso may be more important than the gaze direction.…”
Section: Methodsmentioning
confidence: 98%
“…Currently, it is not very clear how visual perspective taking works. There is debate over whether implicit visual perspective taking is automatic and spontaneous [ 12 16 ], or if it includes a conscious process [ 17 20 ]. Samson et al [ 12 ] showed that incongruent information from another person’s perspective interferes with performance in the Level 1 visual perspective taking task, even when the participant is ignoring that other person (altercentric intrusions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research has shown that the presence of another can also elicit spontaneous level-2 perspective-taking. Ward et al (2019Ward et al ( , 2020 asked participants to perform a mental rotation task that involves making judgements about an object rotated away from oneself. Participants usually have to respond according to some property that would be easier to detect if the object were upright from their perspective.…”
Section: Spontaneous Perspective-takingmentioning
confidence: 99%